A lack of premature termination codon read-through efficacy of PTC124 (Ataluren) in a diverse array of reporter assays. - Stuart P McElroy; Toshifumi Nomura; Leah S Torrie; Emma Warbrick; Ulrike Gartner; Gavin Wood; W H Irwin McLean (PLoS Biology)
The drug molecule PTC124 (Ataluren) has been described as a read-through agent, capable of suppressing premature termination codons (PTCs) and restoring functional protein production from genes disrupted by nonsense mutations. Following the discovery of PTC124 there was some controversy regarding its mechanism of action with two reports attributing its activity to an off-target effect on the Firefly luciferase (FLuc) reporter used in the development of the molecule. Despite questions remaining as to its mechanism of action, development of PTC124 continued into the clinic and it is being actively pursued as a potential nonsense mutation therapy. To thoroughly test the ability of PTC124 to read through nonsense mutations, we conducted a detailed assessment comparing the efficacy of PTC124 with the classical aminoglycoside antibiotic read-through agent geneticin (G418) across a diverse range of in vitro reporter assays. We can confirm the off-target FLuc activity of PTC124 but found that, while G418 exhibits varying activity in every read-through assay, there is no evidence of activity for PTC124.